2022
DOI: 10.1177/03331024221099216
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the ICHD-3 criteria for headache attributed to mild traumatic injury to the head: Insights from the Toronto Concussion Study Analysis of Acute Headaches Following Concussion

Abstract: Background There is limited prospective data on the prevalence, timing of onset, and characteristics of acute headache following concussion/mild traumatic brain injury. Methods Adults diagnosed with concussion (arising from injuries not related to work or motor vehicle accidents) were recruited from emergency departments and seen within one week post injury wherein they completed questionnaires assessing demographic variables, pre-injury headache history, post-injury headache history, and the Sport Concussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moreover, there are multiple precipitant factors for headache, and many of these can be experienced by individuals after a concussion or traumatic brain injury (e.g., adverse psychological reactions to the injury-related circumstances, depressed or anxious mood, parental trauma-related anxiety [ 49 ], sleep deprivation, interrupted sleep, altered sleep–wake cycles, etc.) [ 50 ]. Therefore, the focus of the diagnosis and management of PTH should be on these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are multiple precipitant factors for headache, and many of these can be experienced by individuals after a concussion or traumatic brain injury (e.g., adverse psychological reactions to the injury-related circumstances, depressed or anxious mood, parental trauma-related anxiety [ 49 ], sleep deprivation, interrupted sleep, altered sleep–wake cycles, etc.) [ 50 ]. Therefore, the focus of the diagnosis and management of PTH should be on these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Sound hypersensitivity has been widely described after TBI. 10,[36][37][38][39] A recent prospective study of 302 individuals presenting within one week of a concussion reported photophobia in 74% and phonophobia in 72% of participants, 40 though little information was provided relative to the presence or chronicity of concurrent or pre-existing headache in this study. In contrast, these features have not been as widely studied in PTH.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, photophobia is considered a hallmark feature of the migraine attack, 5 though it is important to clarify that light sensitivity is not unique nor specific to migraine headache. In fact, light sensitivity in association with non‐migrainous headaches is a widely reported consequence of TBI, even in those without a history of migraine 40,43 . Analogously, allodynia, pressure‐sensitivity, and other sensory dysfunction (as discussed above), can be seen in both primary and secondary headache.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it should be investigated whether the concussion screening interventions address the delayed onset of symptoms [ 25 ]. Even a mild head injury or concussion can lead to long-term consequences [ 26 , 27 ]. Delayed effects of these events are common among retired athletes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the risk of traumatic brain injury is higher in contact sports, causes long-term consequences and the recovery from such incidents is longer if the athlete had a history of migraines before the injury [ 11 , 12 , 27 ]. However, limiting physical activity has a negative effect on medical conditions, both physical and mental.…”
Section: Discussionmentioning
confidence: 99%